1987
DOI: 10.1159/000184368
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Renal Mechanisms for Urate Homeostasis in Uremic Patients by Probenecid and Pyrazinamide Test

Abstract: The tubular transport of urate was studied in 47 uremic patients and in 20 normal subjects using probenecid and pyrazinamide tests. There was a marked increase in urate excretion per nephron as the renal function deteriorated. Presecretory reabsorption of urate per nephron, which was almost complete in normal subjects, showed a diminution with increasing severity of chronic renal failure. Until the creatinine clearance had decreased to less than 10 ml/min, the secreted urate per nephron remained almost constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…However, whether these associations are accidental or genetically related could not be elucidated from these cases. As for hyperuricemia, FEUA in all 3 cases was low consistent with the report of Garyfailos et al [11], espe cially in case I, which might suggest the common defect of renal tubular function. Further investigations of this ped igree including HLA typing and chromosome analysis and more information regarding other familial cases are necessary to elucidate the above mentioned problem.…”
Section: Discussionsupporting
confidence: 88%
“…However, whether these associations are accidental or genetically related could not be elucidated from these cases. As for hyperuricemia, FEUA in all 3 cases was low consistent with the report of Garyfailos et al [11], espe cially in case I, which might suggest the common defect of renal tubular function. Further investigations of this ped igree including HLA typing and chromosome analysis and more information regarding other familial cases are necessary to elucidate the above mentioned problem.…”
Section: Discussionsupporting
confidence: 88%
“…Although the results of these studies should be considered cautiously, but as the same test was used in normo-and hyperuricemic patients, the differences among groups are real. The impairment of secretion of urate could not be a consequence of renal insufficiency, because the decline in the glomerular filtration rate pro duces an adaptative decrease in urate presecretory and postsecretory reabsorption, and a later decrease in urate secretion, but only when creatinine clearance is below 10 ml/min [28], In patients with essential hypertension, hyperuricemia was associated with decreased renal plas ma flow [29] and abnormalities in the handling of urate by the kidney. Similar changes to those found in our patients have been described, and it has been suggested that these could be due to involvement of renal vessels [30], Further more, the association of lower excretion of urate with a tendency to retain water and sodium by the kidney sup port the idea that the hyperuricemia in the renal trans plant patients is probably mediated by hemodynamic changes induced by CyA [31], which could be modified by vasodilators.…”
Section: Discussionmentioning
confidence: 99%
“…[14] The response of urate excretion to drugs that alter renal tubular of urate has been used to analyze the tubular mechanisms of urate transport in man by several authors. [3,4,12,[14][15][16][17][18][19][20][21][22][23] However, secretion and reabsorption may occur in the same tubular segments, and may have active and passive components. Reabsorption of filtered and secreted urate may occur at the same or separate sites and by the same or distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The response of urate excretion to PB and PZA has been widely used to analyze the tubular mechanisms of urate transport in normal subjects as well as in patients with renal failure or abnormal urate clearance. [12,13] …”
Section: Introductionmentioning
confidence: 99%